PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU HACKER DENGAN TUJUAN PEMESANAN FIKTIF - Sucia, Fitri; Pamungkas, Andi; Akbar, Ali; Paminto, Saptaning Ruju (Law Department Jenderal Achmad Yani University, 2022)
Advances in science and technology have made the types and forms of crime more sophisticated and diverse. One of the most common crimes is hacking personal accounts with the aim of placing online orders for other people. Criminal liability is carried out to fulfill justice, if you have committed a crime and fulfill the elements specified in the law. The method used in this writing is normative juridical by conducting a study using books, journals, writings and using a case study approach with the decision Number 1597/Pid.Sus/2019/PN.Jkt.Utr, with the aim of seeing how criminal responsibility in Indonesia is against perpetrators. who do Hackers to then place orders online on behalf of other people. Based on the results of the research conducted, it was concluded that the defendant Untung Arif Budiman fulfilled the elements of a criminal offense and was able to take responsibility for the mistakes committed which were against the law so that the judge sentenced the defendant to Article 35 in conjunction with Article 51 paragraph (1) of the Law. Law of the Republic of Indonesia Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 8 of 1981 concerning the Law of Criminal Procedure and other relevant laws and regulations.